Achromic nevus and achromic nevus syndrome. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
The issue discussed by Di Lernia underlines the confusion which characterizes the nomenclature utilized to define hypomelanosis of Ito. In the fìrst description published in a Japanese journaJ (2), lto described a singular case of "bilateral systematized nevus depigmentosus". A year later, he denominated the same case "incontinentia pigmenti achromians" (3). This term was used to stress the morphological similarity with incontinentia pigmenti, which is characterized by a mosaic distribution along the Blaschko's lines. (...).